2022
DOI: 10.3390/ijerph19116610
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Planning and Management of Land Use in River Source Region: A Case Study of Songhua River Basin, China

Abstract: Adjusting land use is a practical way to protect the ecosystem, but protecting water resources by optimizing land use is indirect and complex. The vegetation, soil, and rock affected by land use are important components of forming the water cycle and obtaining clean water sources. The focus of this study is to discuss how to optimize the demands and spatial patterns of different land use types to strengthen ecological and water resources protection more effectively. This study can also provide feasible watersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Compared with other scholars' studies, Duan et al [48] used MOP-PLUS to optimize the simulation of the Songhua River basin in northeastern China, and the final results yielded a decrease in forested land under the economic development scenario, and the results were similar to this paper. However, under the water conservation scenario and the ecological conservation scenario, the forest land increased due to the consideration of functions such as water conservation and biodiversity protection of forest land.…”
Section: The Reduction Of Forest Land In the Study Results Needs To B...supporting
confidence: 75%
“…Compared with other scholars' studies, Duan et al [48] used MOP-PLUS to optimize the simulation of the Songhua River basin in northeastern China, and the final results yielded a decrease in forested land under the economic development scenario, and the results were similar to this paper. However, under the water conservation scenario and the ecological conservation scenario, the forest land increased due to the consideration of functions such as water conservation and biodiversity protection of forest land.…”
Section: The Reduction Of Forest Land In the Study Results Needs To B...supporting
confidence: 75%
“…Land use planning, on the other hand, involves the allocation and regulation of land for various purposes, such as residential, commercial, agricultural, and conservation areas. The integration of these two fields aims to ensure that land use decisions consider the impact on water availability, quality, and ecosystem health [57]. Owing to varying state mandates or owing to local discretion, water planning and land use authorities may function on distinct timetables.…”
Section: Integrated Land Use and Water Management Planningmentioning
confidence: 99%
“…There are significant differences in the carbon sequestration capacity of vegetation and soil in different land-use types [ 5 ], and the interconversion between land-use types will definitely cause an increase or decrease in CS [ 6 ]. However, the carbon sink effect of each land-use type conversion varies in different regions and even shows carbon loss.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated valuation of ecosystem services and trade-offs (InVEST) model has been widely used in the evaluation of CS due to its high operating efficiency, ease of access to data, and high accuracy [ 10 , 11 ]. On this basis, researchers have studied land-use changes and CS at different regional scales, including basins [ 5 , 11 ], administrative districts [ 12 , 13 ], and urban agglomerations [ 4 , 14 ], by combining scenario simulation and InVEST. Numerous studies have shown that higher and more stable CS can be realized by inhibiting blind urban expansion and relying on low land-use transition [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%